Experimentally determined deposition of ambient urban ultrafine particles in the respiratory tract of children. (December 2020) - Guo, Lingli; Salimi, Fahard; Wang, Hao; Hofmann, Werner; Johnson, Graham R.; Toelle, Brett G.; Marks, Guy B.; Morawska, Lidia
Highlights: Respiratory tract deposition of UFPs was measured first time for children at school. Inhaled UFPs were categorized into groups of traffic exhaust and urban background.. Traffic-related UFPs showed higher total deposition fraction than urban background's. Abstract: A critical element of the risk assessment of exposure to airborne ambient ultrafine particles (UFP) is the quantification of respiratory tract deposition (RTD) of the particles, which is intrinsically challenging, particularly at the population scale. In this study, we used a recently proposed method to experimentally determine the RTD of urban UFP in a large group of children exposed to these particles in a school setting in Brisbane, Australia. Children are one of the most susceptible population groups; However, little is known about the deposition of UFP from urban traffic in their airways. In order to advance the knowledge in this field, the objectives of this study were: to determine the deposition of ambient urbane UFP in large number children, to catergorize the source of inhaled UFPs and hence to assess the contribution of air pollution sources to the deposition. RTD was measured in children aged 8–11 at primary schools using a flow-through chamber bag system. First, the inhaled and exhaled air was separated; then the particle number size distribution and particle number concentration were measured. The sources of inhaled UFP were categorized according to their particle number size distribution by a K means cluster technique. A total of 128 children from five schools performed the RTD measurement. The mean total deposition fraction of urban UFP in all children was 0.59 ± 0.10. Inhaled UFP were categorized into two groups: traffic and urban background, with the GMD of corresponding particle number size distribution of 20 nm and 40 nm, respectively. The total deposition fraction (mean ± SD) of UFP from these two groups was 0.68 ± 0.09 for traffic and 0.55 ± 0.08 for urban background respectively. This is the first study in which RTD was measured in a large group of children inhaling real urban UFP. First, we proved that this novel method can indeed be applied easily and quickly to a large group of people. Second, we quantified the RTD of children, thus providing an important input to the risk assessment for exposure to UFP.